Pengaruh Harga Dan Nilai Yang Dirasakan Terhadap Minat Beli Ulang Dengan Keputusan Pembelian Sebagai Variabel Intervening Pada Konsumen Indomaret Di Semarang - Putri, Rizky Meisa; Mahmud, Mahmud; Anomsari, Ariati; Purwatiningsih, Aris Puji (Politeknik Negeri Ambon, 2024)
This study aims to evaluate the impact of price and perceived value on repurchase intention with purchase decisions as a mediating variable for Indomaret customers in Semarang. The methodology used is quantitative with a Partial Least Square (PLS) approach. Information was collected from 112 respondents who shopped at Indomaret through online and offline surveys. The findings of this research imply that purchasing decisions have a significant impact on repurchase intention. Price is proven to have a significant influence on purchasing decisions, but not directly on repurchase interest. On the other hand, perceived value has a significant influence on both purchasing decisions and repurchase intention. Purchasing decisions are proven to be an important mediating variable in the relationship between price and perceived value and repurchase intention. This research provides insight into effective marketing strategies for Indomaret in increasing consumer loyalty amidst tight competition with Alfamart and other retailers. Apart from that, this research also adds contributions to the literature regarding consumer behavior in the Indonesian retail sector.Keywords: Price, Perceived Value, Purchase Decision, and Repurchase Intention.